The Influence of Human Capital on Readiness to Work Digitally 2024 - Damayanti, Safina; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2026)
Good labor absorption in the modern era is strongly supported by equally essential digital capabilities. However, high unemployment rates often remain a persistent challenge in many regions. Alongside digital development, digital human readiness should be strengthened through more systematic and targeted activities. This study aims to analyze the role of human capital and demographic factors in influencing individual digital readiness in Serang Regency. Using microdata from Survey Angkatan Kerja Nasional (SAKERNAS) 2024, this study employs a binary logistic regression model. The empirical result indicate that human capital and demographic characteristics jointly have a significant tendency, explaining approximately 40% of the variation in individuals’ digital readiness for work. Given this significance, the study can serve as a basis for stakeholders to design better individual readiness strategies that, in turn, enhance community welfare.